EMPATI DAN MOTIVASI KERJA GURU SEKOLAH LUAR BIASA - IRIANI INDRI HAPSARI; MARDIANA MARDIANA (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2016)
This study aims to determine the effect of empathy on teachers work motivation in special needs school. The population of this study are the teachers of special needs school. This study uses a quantitative method with the sample amounted to 81 respondents. This study uses two scales which are the scale of teacher’s work motivation and empathy scale. Both of the scale were arranged by researcher based on work motivation theories of Louis George and Tara Sabhapathy. Empathy scale based on empathy theories of The QCAE (a Questionnaire of Cognitive and Affective Empathy). The hypothesis test used in this study using a regression analysis one predictor. Based on the analysis of data, obtained F count 11.272 > F Table 3.96 with p = 0.001 (p < 0.05). Its means there is a significant influence of empathy on teacher’s work motivation in special needs school. The result shows a positive influence which means if there’s a high level of empathy in special need school’s teachers, then the level of work motivation will be high.